Effects of online heutagogy approach in learning science via Telegram towards pupils’ science process skills and creative thinking skills - Abdul Halim, Abdullah; Abd Halim, Noor Dayana (LUMAT: International Journal on Math, Science and Technology Education, 2024)
The COVID-19 pandemic has necessitated the adoption of online learning methods worldwide, including in Malaysia. The Ministry of Education (MoE) in Malaysia has recognized the importance of online learning due to the implementation of Movement Control Order (MCO). However, the limitations of online learning, such as reduced interaction between teachers and pupils, have prompted educators to explore alternative approaches that emphasize self-directed learning. Hence, this study aimed to develop a learning method based on the heutagogy approach using the Telegram platform and examine its impact on science process skills and creative Thinking Skills in primary school pupils. The study employed a quantitative research design with a pre-experimental design and involved 20 Year 5 pupils. Pre-post tests were conducted to assess the skills, and the data were analyzed using descriptive and inferential analysis techniques. The descriptive analysis revealed a mean improvement in both Science process skills and Creative Thinking Skills following the intervention with the heutagogy approach. Furthermore, the inferential analysis confirmed a significant difference between pre- and post-test scores for both skills after integrating the heutagogy approach. The positive findings of this study shed light on the efficacy of the heutagogy approach in online learning, particularly in the context of science education for primary school pupils. These results offer valuable insights to educators who can consider incorporating the heutagogy approach into their teaching practices. By doing so, educators can enhance the learning experiences and outcomes of their pupils in science education.